Assessment of Alteration in Aerobic Conjunctival and Meibomian Gland Microbial Flora after Cataract Surgery and its Association with Postoperative Meibomian Gland Dysfunction - Sonia Bhargav; Surinder Kumar; Tarun Arora (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Combination of various commensal microorganism species is capable of protecting the ocular surface from colonisation by potentially pathogenic microbes. These homeostatic microorganisms can be easily altered by environmental factors like cataract surgery. These may play a role in the development of postcataract surgery Meibomian Gland Dysfunction (MGD), whose exact pathogenesis is still unknown. Aim: To assess the change in aerobic bacterial flora of meibomian glands and conjunctiva and its association with the development of MGD after cataract surgery. Materials and Methods: This prospective clinical study was conducted in Department of Ophthalmology at BPS Government Medical College for Women, Sonepat, Haryana, India, from June 2021 to February 2022. A total of 60 eyes of 60 patients who had undergone uncomplicated phacoemulsification surgery with intraocular lens implantation were selected. Conjunctival and Meibomian Gland (MG) secretions samples were collected preoperatively before starting antibiotics and at six weeks postoperatively. Aerobic bacteria isolated from the culture samples of patients before and after surgery were analysed for microbial flora change (MFC). At six weeks postoperative follow-up visit, the diagnosis of the MGD was made on slit lamp examination of lid margin and meibomian glands. Chi-square test was applied to assess the association between patients with MFC and patients with MGD. Results: There were 33 males and 27 females, with a mean age of 62.41 years. Preoperative conjunctival samples of 20 patients (33.33%) and MG samples of 27 patients (45%) were culture positive for aerobic bacteria. Most common microorganism isolated from preoperative samples was Coagulase Negative Staphylococci (CoNS). Isolation rate of Staphyloccus aureus increased postoperatively in both conjunctival and MG culture samples. Postoperative aerobic Microbial Flora Change (MFC) in culture samples of either conjunctival or MG or both was present in 30 patients (50%). Total 16 patients (26.6%) developed MGD out of which 13 patients (81.25%) had MFC. The association between MFC and MGD was statistically significant (p-value=0.004). Conclusion: There is alteration of ocular aerobic bacterial flora after cataract surgery and it has a statistically significant association with postcataract surgery MGD. Replenishment of ocular surface microflora can play a preventive and therapeutic role in the management of postcataract surgery MGD.